MARMOT: magnetism, anisotropy, and more, using the relativistic disordered local moment picture at ﬁnite temperature - Patrick, C; Staunton, J (IOP Science, 2022)
We present MARMOT, a hybrid Python/FORTRAN implementation of the disordered local moment picture within multiple scattering density-functional theory. MARMOT takes atom-centred, scalar-relativistic potentials and constructs an eﬀective medium (within the coherent potential approximation) to describe the disordered magnetic moment orientations at ﬁnite temperature. By solving the single-site scattering problem fully relativistically, spin-orbit eﬀects are included, allowing the magnetocrystalline anisotropy to be calculated. Magnetic transition temperatures, spin and orbital moments, the density-of-states, and analytical parameterizations of the magnetic potential energy surface can also be calculated. Here, we describe the theory and practical implementation of MARMOT, and demonstrate its use by calculating Curie temperatures, magnetizations and anisotropies of bcc Fe, GdFe2 and YCo5.